2019
DOI: 10.1007/s12264-019-00381-w
|View full text |Cite
|
Sign up to set email alerts
|

White Matter Abnormalities in Major Depression Biotypes Identified by Diffusion Tensor Imaging

Abstract: Identifying data-driven biotypes of major depressive disorder (MDD) has promise for the clarification of diagnostic heterogeneity. However, few studies have focused on white-matter abnormalities for MDD subtyping. This study included 116 patients with MDD and 118 demographically-matched healthy controls assessed by diffusion tensor imaging and neurocognitive evaluation. Hierarchical clustering was applied to the major fiber tracts, in conjunction with tract-based spatial statistics, to reveal white-matter alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 40 publications
(44 reference statements)
1
17
0
Order By: Relevance
“…Results of the present study also suggest that patients with MDD mainly exhibit two subtypes with dysfunctional connectivity of the DMN, which are identified in a large multi-site sample and replicated in an independent single-site dataset. Our prior study also reported that subtype of MDD with widespread white-matter abnormalities had more neurocognitive deficit ( Liang et al, 2019 ). Findings of subtypes with distinct profiles of brain abnormalities may reveal the potential neurobiological substrates of key sources of heterogeneity in depression ( Price et al, 2017a , Williams, 2016 ).…”
Section: Discussionmentioning
confidence: 78%
“…Results of the present study also suggest that patients with MDD mainly exhibit two subtypes with dysfunctional connectivity of the DMN, which are identified in a large multi-site sample and replicated in an independent single-site dataset. Our prior study also reported that subtype of MDD with widespread white-matter abnormalities had more neurocognitive deficit ( Liang et al, 2019 ). Findings of subtypes with distinct profiles of brain abnormalities may reveal the potential neurobiological substrates of key sources of heterogeneity in depression ( Price et al, 2017a , Williams, 2016 ).…”
Section: Discussionmentioning
confidence: 78%
“…The acute effects of psychedelics resemble some of the positive symptoms (i.e., hallucinations and delusions) in patients with schizophrenia ( Vollenweider et al, 1998 ; Schmid et al, 2015 ), and chronic LSD administration alters rat frontal cortex expression of a group of genes relevant to schizophrenia ( Martin et al, 2014 ). Markers linked to white matter structural changes, which have been associated with depression ( Liang et al, 2019 ), were also significantly altered upon DOI administration.…”
Section: Discussionmentioning
confidence: 99%
“…The acute effects of psychedelics resemble some of the positive symptoms ( i.e ., hallucinations and delusions) in patients with schizophrenia ( 50, 51 ), and chronic LSD administration alters rat frontal cortex expression of a group of genes relevant to schizophrenia ( 59 ). Markers linked to white matter structural changes, which have been associated with depression ( 60 ), were also significantly altered upon DOI administration. We identified genetic substrates associated with depression in the epigenomic landscapes of DOI exposure, but the concurrence of genetic markers for schizophrenia may serve as a molecular warning on the risks associated to the use of psychedelics in psychotic-prone individuals.…”
Section: Discussionmentioning
confidence: 99%